LncRNA LYPLAL1, miR-204-5p, and SIRT1: novel signatures for risk assessment of diabetic macrovascular complications - Maysa A. Mobasher; Marwa A. Shabana; Mousa O. Germoush; Najlaa Yousef Abuzinadah; Amir Abd-elhameed; Shereen A. Baioumy; Moataz A. ElKot; Marwa M. Esawy (Scientific Reports)
Abstract Long-term, uncontrolled diabetes mellitus can lead to micro- and macrovascular problems. The protective function of lncRNA LYPLAL1 is to reduce endothelium cell inflammation by upregulating sirtuin 1 (SIRT1) and reducing microRNA (miR)-204-5p. This work attempted to examine the lncRNA LYPLAL1/miR-204-5p/SIRT1 molecules as diagnostic biomarkers for diabetic MVC and to assess their clinical correlations. The study enrolled 32 controls, 32 patients with diabetes alone, and 32 patients with diabetic MVC. RT-qPCR, or quantitative real-time PCR, was utilized to determine the expression levels of lncRNA and miR. SIRT1 was measured by ELISA. When comparing cases with MVC to those without MVC, the lncRNA LYPLAL1 and SIRT1 values were significantly lower. Conversely, patients with MVC had significantly higher miR-204-5p levels than those without MVC. The LncRNA LYPLAL1 performed best in terms of detecting MVC. It attained 90.6% specificity and 96.9% sensitivity. A combination of three markers (lncRNA LYPLAL1, miR-204-5p, and SIRT1) yielded the best accuracy at 98.4%. LYPLAL1 expression appeared to be an independent MVC predictor. Adjusted OR for LYPLAL1 expression was 405 (95% CI: 1.4–1200) (p = 0.039). When we compared cases with MVC to those without MVC, the lncRNA LYPLAL1 and SIRT1 values were significantly lower. Patients with MVC had significantly higher miR-204-5p levels than those without MVC. LYPLAL1 LncRNA demonstrated the best performance characteristics. LncRNA LYPLAL1 expression is an independent predictor of MVC.